Factors important in bone union after posterior lumbar interbody fusion using the cortical bone trajectory technique - Yanai, Yoshihide (J Spine Surg, 2020)
BACKGROUND: The cortical bone trajectory (CBT) technique has developed as an alternative to the traditional pedicle screw fixation technique due to its minimum invasiveness for screw insertion and rigid fixation for posterior lumbar interbody fusion (PLIF). However, the factors contributing to bone union after CBT-PLIF is a controversial subject. The aim of this study was to investigate factors important to bone union after CBT-PLIF METHODS: We analyzed 69 consecutive patients who underwent single-level CBT-PLIF from October 2011 to December 2016 and were followed for over two years. Bone union was evaluated using computed tomography (CT) and dynamic assessment in the radiograph within two years after CBT-PLIF. The following factors that may influence bone union were investigated: age, gender, bone mineral density (BMD), cage materials [polyether-ether-ketone (PEEK) or titanium (Ti)], vertebral-slip (neutral), translational motion (flexion/extension), angular motion (flexion/extension), screw depth into the vertebral body (% depth), interval of bilateral screw heads, and cage position. RESULTS: The bone union rate at the two-year follow-up was 88.4% (61/69). A univariate analysis revealed that variables with values of P<0.20 were age (P<0.01), gender (P=0.07), cage material (P=0.18), vertebral slip (neutral) (P=0.14), % depth (P=0.086), and cage position (P<0.01). Multiple logistic regression analyses revealed that factors related to bone union were young age (P<0.01), Ti cage (P<0.01), small vertebral slip (neutral) (P<0.01), high % depth (P<0.01), and anterior cage position (P<0.01). CONCLUSIONS: For CBT-PLIF, deeper screw insertion into the vertebral body, anterior cage placement, and Ti cage usage may be important surgical techniques to achieve a successful bone union.